"Talk about sex?": Therapists' experience of facilitating discussion of the topics of gender and sexuality in therapy. Issue 4 (2nd October 2022) - Naughton, Terry
ABSTRACT: Sexuality is a key element of the life of any human being. The present study aims to explore therapists' experience of facilitating discussion of the topics of gender and sexuality in therapy. The design consisted of a qualitative approach using semi-structured in-depth interviews with five participants. Interpretative Phenomenological Analysis (IPA) was used to analyse the transcripts where themes were identified. The results highlighted two superordinate themes and five sub-themes. The first superordinate theme is View from Within with three sub-themes: personal processing, level of comfort and self of the therapist. The World Outside is the second superordinate theme and it includes subthemes of therapy training and facilitating discussion of the topics. Conclusions highlighted that overall, therapists facilitate discussion of matters relating to gender and sexuality with clients. However, they feel unprepared by their training and may be reluctant to engage because of a lack of comfort and knowledge. An awareness of their own facilitation, personal processing and experiences enhances this offering. Despite certain challenges, the findings of this study suggest that therapists engage with these topics and this concurs with existing research.